Safety and Efficacy of Bedaquiline-Pretomanid-Linezolid (BPaL) in Patients with Drug-Resistant Tuberculosis: (Review from Clinical Evidence) - Oki Nugraha Putra; Ana Khusnul Faizah; Nani Khusnul Wijayanti DN (STIKES Rumah Sakit Anwar Medika, 2023)
Regimens containing bedaquiline were administered for up to 11 months and 24 months in shorter and longer regimen to treat patients with drug-resistant tuberculosis (DR-TB), respectively. Pre XDR and XDR-TB are highly DR-TB with a lower success treatment than MDR-TB. Therapy for highly DR-TB with fewer drugs and shorter treatment is required to increase success treatment. Bedaquiline-pretomanid-linezolid (BPaL) is considered to be used for highly DR-TB. This was a narrative review summarize the efficacy and safety of the BPaL regimen to manage patients with highly DR-TB. The 26-week of BPaL regimen was reported to provide favorable outcomes in two previous trials, Nix and Zenix TB. BPaL offers treatment success, especially in highly drug-resistant tuberculosis compared to standard regimens containing bedaquiline. Nonetheless, adverse effects, such as hematologic toxicity or myelosuppression, peripheral neuropathy, and optic neuritis were more common in BPaL regimens than in standard regimens. The incidence QT prolongation was lower with BPaL regimens compared with standard regimens. Adding pretomanid to the bedaquiline-linezolid regimen prevents TB bacteria that are resistant to bedaquiline. It is necessary to periodically monitor adverse effects associated with linezolid in BPaL regimen and how to manage them accordingly. This review concludes that the BPaL regimen provides favorable outcomes, reduces pill burdens, and shortenes treatment. Health facilities should prepare for the implementation of BPaL to manage DR-TB patients. Keywords: Drug-resistant TB, BPaL, Efficacy, Safety